2019
DOI: 10.1088/1755-1315/270/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Observation of morphological and physiological characteristics on Abangares Mahogany (Swietenia macrophylla King.) In South Sulawesi

Abstract: The one of identification system using morphophysiological analyses for breeding program Mahogany is needed. Mahogany (Swietenia macrophylla) is a tree species which is easy to cultivate as it is able to thrive in a great variety of habitats and soil types. Here, we present a study on the relationship between morphological and physiological parameters on S. macrophylla. The study was carried out in a seed orchard of Mahogany in genetic resource area of 2nd Forest Seed/Seedling Office, Gowa district, South Sula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…As presented in Table 1, the Large-leaf Mahogany (S. macrophylla, King) has the highest counts, and only 1 shrub species is present, the Makahiya (Mimosa pudica, L.) that grows abundantly in tropical places (Ahmad et al 2012;Larekeng 2019). There were 4 tree species, and 1 herb species which are still unnamed.…”
Section: Resultsmentioning
confidence: 99%
“…As presented in Table 1, the Large-leaf Mahogany (S. macrophylla, King) has the highest counts, and only 1 shrub species is present, the Makahiya (Mimosa pudica, L.) that grows abundantly in tropical places (Ahmad et al 2012;Larekeng 2019). There were 4 tree species, and 1 herb species which are still unnamed.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the leaves that appeared were not counted in this study because they were too small and young (just developing). Although the internodes have been formed, the leaves have not fully developed yet, and the characters are difficult to observe [14]. Therefore, immature leaves do not need to be counted when characterizing the morphology of a plant.…”
Section: Morphological Character Of D Alata Stemmentioning
confidence: 99%
“…Fig. 3a shows two leaf color variations in the six observed accessions of D. alata which are pale green (30%) and dark green (40%), while three accessions (30%) could not be identified because the leaf size was too small due to new development and the morphology is not clear yet [14]. The results showed that the color of the leaf margins was identified as two groups of variations which are green (60%) and purple (10%) (Fig.…”
Section: Fig 2 Frequency Of Observed Leaves Of D Alatamentioning
confidence: 99%
“…Budidaya dilakukan dengan iklim kering dan diperlukan sistem pengairan yang baik. Studi melaporkan tanaman dari spesies yang sama tumbuh di lingkungan yang berbeda dapat menghasilkan konsentrasi yang berbeda dari senyawa metabolit sekunder (17). Peneliti tidak turut terlibat langsung dalam budidaya tanaman mahoni, sehingga kondisi lingkungan dan iklim tempat tumbuh mahoni yang digunakan tidak diketahui secara jelas.…”
Section: Hasil Penelitian Danunclassified